2021
DOI: 10.3390/children8020156
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Weight Status and Autonomous Motivation towards Sports among Children with Various Profiles of Motor Competence and Organized Sports Participation

Abstract: This study aimed (1) to identify profiles in children based on actual motor competence (AMC), perceived motor competence (PMC), and organized sports participation (OSP), and (2) to examine differences among these profiles in weight status as well as autonomous motivation towards sports. Children’s (N = 206; 112 boys; Mage = 10.83 ± 0.92 years) AMC, PMC, OSP, weight status, and autonomous motivation towards sports were measured using validated assessment tools. Cluster analyses identified three profiles with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 59 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…To address Ulrich's concerns, Rudisill and colleagues (Rudisill, Mahar, & Meaney, 1993) developed, a few years later, a scale to measure the accuracy with which children perceive their MC. Other scales have been developed more recently to integrate PMC with matching motor tasks (Barnett, Vazou, et al, 2016;Tietjens et al, 2018), coined as aligned product-oriented measure of PMC (Coppens et al, 2021). The need for aligned instruments of MC and PMC has been further highlighted by Estevan and Barnett (2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To address Ulrich's concerns, Rudisill and colleagues (Rudisill, Mahar, & Meaney, 1993) developed, a few years later, a scale to measure the accuracy with which children perceive their MC. Other scales have been developed more recently to integrate PMC with matching motor tasks (Barnett, Vazou, et al, 2016;Tietjens et al, 2018), coined as aligned product-oriented measure of PMC (Coppens et al, 2021). The need for aligned instruments of MC and PMC has been further highlighted by Estevan and Barnett (2018).…”
Section: Introductionmentioning
confidence: 99%
“…These have shown that, in general, children tend to overestimate their skills and that children with greater MC tend to be more accurate in the perception of their affordances (Almeida, Luz, Martins, & Cordovil, 2017). Recently, the relationship between PMC and actual MC in children has been explored using a person-centered approach, that is, using cluster analysis, with PMC measure aligned with actual MC (Coppens et al, 2021;Estevan, García-Massó, Molina García, & Barnett, 2019Niemistö et al, 2022). Weiss and Amorose (2005) originally developed this methodology to analyze whether children estimated their MC accurately/inaccurately.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Psychological factors play an important role in beginning and continuing organized sports participation. 10 Physical literacy provides a theoretical framework to understand the association between organized sports activities and people's physical and psychological well-being. More specifically, physical literacy is described as the physical competence, motivation, confidence, knowledge, and understanding to value and take responsibility for engagement in physical activities (ie, organized sports activities) for life.…”
mentioning
confidence: 99%
“…Before children with SCD start participating in organized sports activities, assessment of their physical competence is advised to avoid any risk of vaso-occlusive episodes 3 . Psychological factors play an important role in beginning and continuing organized sports participation 10 . Physical literacy provides a theoretical framework to understand the association between organized sports activities and people’s physical and psychological well-being.…”
mentioning
confidence: 99%